Does Price Influence on Shop Purchase Decisions? - Fakhri, Rizqi (Adpebi International Journal of Multidisciplinary Sciences, 2023)
Objective– The purpose of this study is to determine the effect of price on purchasing decisions in purchasing Happy Soya cooking oil at PT Indofood Sukses Makmur PekanbaruMethodology/approach– Sources of data obtained from primary and secondary data. the total population is 84 shops, while the number of samples is also 84 shops, the sampling technique is total sampling. Data analysis is descriptive and quantitative, in the form of hypothesis testing.Findings– The results of the study show that both the partial test that prices affect the shop's decision to buy goods. And the magnitude of the influence of the price variable on the purchasing decision variable is 24.70%. Meanwhile, the remaining 75.30% is influenced by other variables outside the price variable which are not examined in this study.Novelty/value– That the price variable has a negative direction towards purchasing decisions. Each increase in the price of one unit will reduce the purchase decision, and vice versa, each decrease in the price of one unit will increase the purchase decision.